(untitled) (Development Service Industry Management, 2024)
The issues of the image of the territories are gaining relevance, as they affect the competitiveness and attractiveness of the territory, the well-being and standard of living of the population. The formation of territory branding creates favorable conditions for attracting resources, allows to form the image of a tourist destination, promotes product differentiation, expansion of the target audience, as well as the conquest of new segments of the consumer market, as a result of which a stable positive image is formed in the minds of consumers associated with a specific territory. Therefore, the formation of the brand will make it possible to effectively use competitive advantages, the tourist potential of the region, and achieve a high level of competitiveness. The purpose of the publication is to analyze the place, role, features of formation and functioning of branding of tourist destinations in the process of their development. The article explores issues related to the role of the tourism industry, the essence of territory marketing, and brand features. It is noted that the central link of modern methods of marketing promotion of territories with significant tourist potential is "branding". The essence of the categorical concept of "territory branding", "destination branding" is defined, the characteristics of the territory brand, approaches to branding of tourist destinations are given. It is noted that the basis of territory branding is formed by uniqueness, inimitability, which leads the consumer to believe that such a territory does not exist. It is justified that when developing a destination brand, it is necessary to take into account what product the destination can provide to the consumer. A mechanism for creating an effective tourist destination brand has been developed. The innovative component of tourist destination branding is considered. A successful brand of a tourist destination is the choice of society, the property of everyone, the intellectual property of society, on which the guaranteed future of tourist regions depends.